Analisis Faktor Yang Mempengaruhi Kejadian Persalinan Kala II Memanjang - Pratamaningtyas, Susanti; Suwoyo, Suwoyo; Oktaviana, Ayu (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2019)
The second stage elongated labor is the phase of a stucked labor and lasts too on the normal process was 2 hours in primigravida and 1 hour at multigravida. The second stage elongated labor cause dehydration, infection, fatigue and IUFD maternal and fetal asphyxia. Many factors affected the incidence including age, parity, spacing of pregnancy, the fetus is large and the location of the fetus. The purpose of this study was to determine the factors associated with the second stage elongated labor. This design was a cross sectional study. Total sample was 49 respondents determined by simple random sampling. The data were analyzed by chi-square test used error level ? 5% . The result of statistical test showed that X2 price was 3,841 which means there was a relations between the variables of age, parity, spacing of pregnancy, fetal weight, and fetus location on second stage elongated labor. Based on these results, it should be identifying the other factors that affecting the second stage elongated labor. Keywords: Second Stage Elongated, Distance Pregnancy, Fetal weight and location of Fetus